OC-111 Diagnostic yield of endoscopic ultrasound (EUS) in the evaluation of idiopathic pancreatitis. a single tertiary referral centre experience. (22nd June 2015) - Saleem, R; Raja, O; Aujla, UI; Devlin, J
Abstract : Introduction: Idiopathic acute pancreatitis (IAP) represents a diagnostic and therapeutic challenge. IAP is prone to high recurrence and understanding its aetiology may assist in preventing recurrent episodes and its related morbidity and mortality. Appropriate investigations help to determine the underlying aetiology and can guide further effective management. We describe our experience to evaluate the role of endoscopic ultrasound (EUS) in patients with unexplained acute pancreatitis in whom cross sectional imaging and conventional laboratory testing had failed to identify the aetiology in a tertiary pancreatico-biliary referral centre. Method: We retrospectively identified all patients who underwent EUS for assessment of idiopathic acute or recurrent pancreatitis during the period Jan 2007–Dec 2013. All patients had appropriate radiological investigations and no underlying cause identified on transabdominal ultrasound, computed tomography (CT) and on magnetic resonance cholangiopancreatography (MRCP). Patients with risk factors known to precipitate pancreatitis including alcohol excess, medications, metabolic or autoimmune conditions, were excluded. Results: 44 patients (male 32, female 12) were identified with a mean age of 50 years (range 21–79 years). 33 (75%) patients had recurrent attacks of acute pancreatitis whereas 11 (25%) patients were referred for EUS after a single attack of acute pancreatitis. EUS revealed a cause of pancreatitis in 21/44 (47.7%) patients. Pancreatic duct stones were detected in 10 (22.7%); biliary duct microlithiasis in 4 (9%); pancreatic divisum in 3 (6.8%) and peri-ampullary lesions in 2 (4.5%) patients. One each had a pancreatic duct stricture, biliary duct stricture and one patient was diagnosed with IPMN (intra-papillary mucinous neoplasm). No underlying cause could be found in 23 (52.3%) patients. Conclusion: EUS demonstrated aetiology in almost half of patients with unexplained acute or recurrent pancreatitis. Our findings support the emerging evidence that EUS is a valuable diagnostic tool in the evaluation of patients with idiopathic pancreatitis and should be considered where initial diagnostic workup including cross sectional imaging remains inconclusive. Disclosure of interest: None Declared.